Avaliação das complicações transanestésicas comparando a infusão contínua peridural versus analgésica em cães submetidos a neurocirurgias - Galindo, Victor; Silva Herculano, Lícia Flávia; Schopf Pasini, Jessika; Vaccarin, Charline Vanessa; Mazzanti, Alexandre; Vasconcelos Soares, André (Pubvet, 2020)
Neurosurgeries have become more frequent in veterinary hospitals, however, there are some questions regarding anesthetics protocols and analgesic techniques. Thus, patient analgesia and hemodynamic stability play a key role in pre, post, and perioperative moments favoring an adequate recovery. This study aimed to evaluate the transanesthetic complications reported on anesthetic records of dogs submitted to hemilaminectomies in the university veterinary hospital of the Federal University of Santa Maria (UFSM) between January 2016 and August 2017, and compare three different analgesic protocols most commonly used in the routine for this surgery. In addition, transanesthetic parameters for each dog were equally recorded in five-minute intervals: cardiac frequency (FC), respiratory frequency (f) blood oxygen saturation (SpO2), mean artery pressure (PAM), temperature and end tidal CO2 (EtCO2). The patients were divided into three groups: Group M: animals receiving epidural analgesia with morphine 0.1mg/kg diluted in 0.26 ml/kg of saline solution 0.9%; Group FLK: bolus of fentanyl 2 μg/kg, lidocaine 1 mg/kg, and ketamine 1 mg/kg followed by infusion of fentanyl 0.1 μg/kg/min, lidocaine 50 μg/kg/min and ketamine 10 μg/ kg/min; and Group F: bolus of fentanyl 2 μg/kg followed by infusion of fentanyl 0.1 μg/kg/min. ANOVA was used to evaluate the anesthetic protocols complications, followed by Tukey’s post-hoc test with a significance level of 5% (p 45mmHg). With this study, it was observed that the use of continuous infusions of FLK, fentanyl, and epidural analgesia with morphine, in the used doses, were effective and safe in the dogs submitted to neurosurgeries, however, it was noticed that the use of morphine caused a greater reduction in temperature during the intraoperative period.